Dyeing of Polyester Fabric with Natural Colorants Extracted from Mahogany (Swieteniamahagoni) Seed Pods (Journal of Engineering Science, 2020)
Polyester fabric is usually dyed with disperse dyes which has severe limitations specially toxicity and environmental issues. The aim of the present research is to introduce an ecofriendly dyeing process for polyester fabric with natural dyes. The natural colorants were extracted from mahogany seed pods using the simple acid boiling method. The spectroscopic analysis of the crude extract was carried out by UV and IR spectra of the extracted dyes and illuminated the presence of natural tannins as coloring materials in the crude extract. 10g fabric was dyed in 200cc extracted solution at 130⁰C for 60 minutes in exhaust dyeing method followed by neutralization and soaping. Finally, a light brown dyed fabric was obtained. The dyed fabric exhibited color strength in terms of k/s value of 0.63 (λmax 360nm), lightness of 80.565 and chromaticity value of 12.002 CIE units. Different samples were dyed by fluctuating the dyeing period. The dyeing traits of the dyed materials were judged in terms of their color strength and fatness properties. All testes were carried out following the ISO standards. From the results, it is lucid that the dyed fabric showed acceptable color fastness properties in case of all fastness except color fastness to light. It is observed that dyeing time had profound influence on the color strength (k/s value) of the dyed material. The k/s value increases with the increase of dyeing period up to 120 minutes. The maximum color strength (0.76) was noted for the fabric. The shorter dyeing time produces lighter samples and the longer dyeing time produced colorful samples.Journal of Engineering Science 11(1), 2020, 37-42